Education Program to Enhance Parents' Knowledge of Caring for Children with Type One Diabetes Mellitus - Razzaq Jawad, Saeed; Hadi Hussein, Kahtan (Journal of Neonatal Surgery, 2025)
Type one diabetic is a major metabolic disease that effect on children It is distinguished by increase glucose level in blood result of insulin secretion defect, It can be diagnosis by plasma glucose intolerance, HbA1c and fasting blood glucose. It lead to a major complications as blindness, amputation, etc. The study objectives are to identify parent's knowledge towards diabetic children and to find-out the relationship between parent's knowledge and socio-demographic characteristic. Material and method A quasi experimental study is carried to describe effectiveness of the educational program upon parents knowledges toward your diabetic children care in the diabetic and endocrine center of Al-Najaf Al-Ashraf city by use the method of pretest/ posttest 1 then posttest 2 by application it on both study group and control group for the period of july.28/ 2024 until October. 10/2024. Study Results: Finding revealed parents knowledge level of study group altered significantly (P<0.05), where before performing educational program sessions the knowledge mean was (1.18) then became after the application of educational program sessions (1.65) and in post-test two the mean became (1.66), while the parents knowledge in control group stayed the same without any change. the research explained the major children age group in both groups with (6-10 years). The parents knowledge in experimental group in posttest1 &2 is elevating, this indicated the educational program was effective interventional approach to improve parents knowledge. Also finding refer to a scientific association between parent knowledge and demographic data in disease period, father and mother Educational level